Improving security performance of healthcare data in the Internet of medical things using a hybrid metaheuristic model - Ashok, Kanneboina; Gopikrishnan, Sundaram (Zielona Góra: Uniwersytet Zielonogórski)
Internet of medical things (IoMT) network design integrates multiple healthcare devices to improve patient monitoring and real-time care operations. These networks use a wide range of devices to make critical patient care decisions. Thus, researchers have deployed multiple high-security frameworks with encryption, hashing, privacy preservation, attribute based access control, and more to secure these devices and networks. However, real-time monitoring security models are either complex or unreconfigurable. The existing models` security depends on their internal configuration, which is rarely extensible for new attacks.
Keywords: medical information systems; Internet of Things (IoT); electronic medical records; information security; metaheuristic optimization; blockchain; quality of service